The Influence of a Lubricant Medium on the Development of Fretting Wear in an Interference Fit Connection - Dalibor Barta; Sławomir Kowalski; Ján Dižo; Aleš Dittrich (Lubricants)
Fretting wear is a phenomenon occurring in many engineering objects, including push fit connections. In view of a large number of factors conducive to wear development, it is difficult to describe the mechanism of wear initiation and development. Therefore, various methods are sought to limit wear development. The use of a lubricant may be one of those ways. The aim of this article is to present the results of testing the influence of a lubricant medium on the development of fretting wear in interference fit connections. As a lubricant medium, MoS2 and Whitmore greases were used. For that purpose, wear tests were first conducted on the shaft/sleeve tribological kinematic pair, and then observations and laboratory measurements were performed. The observations demonstrated the presence of fretting wear traces on all tested samples, irrespective of the tribological kinematic pair being tested. The main kind of damage consisted of material build-ups which, during operation, become oxidised and, while moving along the connection, caused local abrasion and micropits. The best results in restricting the development of fretting wear were achieved with Whitmore grease.